Pengaruh Aplikasi Pupuk Organik dan Mikoriza terhadap Vigor Benih Kakao Terdeteriorasi - Sasmita, Kurnia D; Sobari, I (Seminar Nasional Lahan Suboptimal, 2022)
Sasmita KD, Sobari I.  2022. The effect of organic fertilizer and mycorrhiza application on the vigor of deteriorated cocoa seed. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 263-273. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The location of the source of cocoa seeds, which is far from the nursery, needs a proper seed storage process to prevent seed damage due to the delay in sowing. During storage, cocoa seeds undergo various processes that affect the content of their food reserves and have an impact on seed germination and vigor. The decrease in seed viability due to storage is unavoidable, but maintaining its vigor can be achieved by using appropriate planting media with the application of organic fertilizers and arbuscular mycorrhizal fungi (AMF). This study aimed to examine the effectiveness of organic fertilizers and AMF application on planting media in improving the vigor of deteriorated cocoa seeds due to storage. The experiment was conducted at the Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, West Java, from January to August 2020. The research design used was a split-split plot with three replications. The main plot is the application of organic fertilizers, consisting of: without organic fertilizers and with organic fertilizers. Sub-plots were seed storage, consisting of: without storage and two weeks of storage, while sub-plots were AMF applications, consisting of: without AMF, AMF A, and AMF B. The parameter observed was the vigor of cocoa seedlings. The experiment results showed that the application of organic fertilizers was able to increase the number of leaves, shoot dry weight, and root loss ratio in deteriorated seedlings that were stored for two weeks. AMF application was able to increase the leaf width in seeds that were not stored, but AMF did not improve the vigor of seeds that underwent storage.Keywords: media tanam, penyimpanan benih, pertumbuhan benih.